In vitro propagation of lemon verbena: a plant native of South America - Marcos Vinícius Marques Pinheiro; Daniele Cristina Fontana; Jullie dos Santos; Matheus Milani Pretto; Gabrieli Cristina Vitalli de Azevedo; Denise Schmidt (Acta Scientiarum. Biological Sciences, 2019)
In vitro propagation increases the supply and commercialisation of products of interest. For this, optimising the growing conditions and the composition of the culture medium is crucial to benefit the full development of the plants. Thus, the objective was to evaluate the in vitro propagation of Aloysia triphylla on different culture media, with varying agar and sucrose concentrations. The experiment was conducted as a completely randomised design, 3×3×3 factorial scheme, with three culture media (MS, JADS and WPM), three sucrose concentrations (8, 10 and 12 g L-1) and three agar concentrations (15, 30 and 45 g L-1), with three replicates each and experimental units composed of one plant per replicate. After 25 days of cultivation, the fresh and dry mass of the plants, numbers of leaves, numbers of nodes, plant lengths, numbers of oxidised leaves, hyperhydricity and acclimatization percentages were evaluated. The WPM medium resulted in a reduced fresh mass, reflecting in the low hyperhydricity observed in the explants, and favoured the acclimatization of the plants. Thus, the WPM medium with sucrose (15 g L-1) and agar (12 g L-1) is recommended as the medium most suitable for the in vitro regeneration of Aloysia triphylla.